Induction and characterization of polyploids from seeds of Rhododendron fortunei Lindl. - Lan MO; Jun-hao CHEN; Fei CHEN; Qiang-wei XU; Zai-kang TONG; Hua-hong HUANG; Ren-hui DONG; Xiong-zhen LOU; Er-pei LIN (Journal of Integrative Agriculture, 2020)
Most Rhododendron species are ornamental flowering species widely distributed in Asia, North America, and West Europe. Rhododendron fortunei, one of the endemic Rhododendron species in China, has beautiful flowers with bright colors and is being exploited to meet the needs of the flower market. Polyploid plants usually show superiority in growth, disease resistance, and adaption over their diploid relatives. Here, we report the first case of polyploid induction in R. fortunei. In order to induce polyploidy in R. fortunei, germinating seeds were treated with different concentrations of oryzalin for 16 h. By evaluating ploidy level with flow cytometry, a total of 34 polyploid R. fortunei lines, including 27 tetraploid lines and seven octoploid lines, were obtained. A comparison of treatments indicated that 7.5 mg L−1 oryzalin was the optimal concentration for polyploid induction in seeds of R. fortunei. Compared with diploid plants, tetraploid and octoploid plants exhibited slower growth rates and had thicker and rounder curled leaves with more leaf epidermal hairs. Moreover, larger stomata at lower density were also observed in the leaves of polyploid plants. Chlorophyll contents were also significantly increased in polyploid plants, which leads to a darker green leaf color. Both small and large individuals exhibiting the same characteristics were observed among the obtained tetraploid plants. Overall, our study establishes a feasible method for polyploid induction in R. fortunei, thus providing a basis for breeding new R. fortunei varieties.